Assessing and mitigating large wood‐related hazards in mountain streams: recent approaches. Issue 2 (25th August 2017) - Mazzorana, B.; Ruiz‐Villanueva, V.; Marchi, L.; Cavalli, M.; Gems, B.; Gschnitzer, T.; Mao, L.; Iroumé, A.; Valdebenito, G.
Abstract : The assessment and mitigation of floods in mountain streams, when large wood (LW) is transported, pose several challenges. The process chain consisting of flood propagation, LW recruitment, entrainment, transport, and entrapment triggers, at critical sections such as bridges, unexpected and exacerbated impacts to the exposed built environment. We provide a review on the recent advances in modelling LW dynamics during extreme river floods through computational approaches. Moreover, we describe how scaled flume experiments can enhance process understanding at critical flow sections such as bridges to address risk mitigation problems. Additionally, we present a framework based on Formative Scenario Analysis (FSA) to allow for expert knowledge integration and to subsequently derive consistent hazard process scenarios in steep mountain streams where the application of computational approaches is less reliable. Finally, we discuss how the application of the presented set of assessment methods can support integral flood risk management by explicitly considering LW dynamics since the effectiveness of mitigation critically depends on the acquired process understanding.